THE EFFECT OF FINANCIAL LITERATION LEVELS ON THE USE OF ATM (AUTOMATED TELLER MACHINES) IN COMMUNITIES IN SUBANG CITY - Beby Aryanti; Estu Widarwati; Nunik Nurmalasari (JABI (Journal of Accounting and Business Issues), 2019)
Economic development has been followed by payment system. The evolution of payment system was begin from change system barter, money commodity,cash, coin, check and other banking products such as ATM cards. Benefits of using an ATM card are either directly or indirectly affecting a person's behavior in consumptive consumption activities. This consumptive lifestyle factors, it seems that they do not apply financial literacy in making financial decisions in their daily lives. Meanwhile, sufficient financial management skills and knowledge of financial literacy have a very important role at a young age. The method of research conducted by the authors in this final project is a quantitative descriptive method by using a simple linear regression analysis tool using 100 respondents ATM users in the city of Subang. Statistical methods for testing data using SPSS 22 for windows. By using simple linear regression analysis, the result of equation Y = 16,714 + 0,338X1 + e. From the results of the research note that the financial literacy influential significanly on the use of ATM